EXPERIMENTAL STUDY ON IRRIGATION UNIFORMITY OF SOLID-SET SPRINKLER IRRIGATION UNDER LOW PRESSURE SYSTEM - OSMAN MOHAMED, MANAL ALI (2015)
Solid-set sprinkler irrigation has been widely used around the world. The use of high operating pressure in the operation of sprinkler irrigation system is most prevalent than the use of low operating pressure. Some researchers attempted to use the low operating pressure in some types of sprinkler irrigation system such as center-pivot system. However, the use of low pressure in solid-set sprinkler irrigation is still not applicable. This research aimed to investigate the irrigation uniformity of solid-set sprinkler irrigation using low operating pressure. This study further aimed to develop better understanding about the effect of design factors on irrigation uniformity. Furthermore, to find the relation between water application uniformity on the soil surface and soil moisture distribution uniformity in two soil layers. Two solid-set sprinkler systems, square (12x12 m) and rectangular (12x10 m) were designed. Different low operating pressures (62, 82, 102, and 122 KPa) with different nozzle diameters (4, 5, 6 and 7 mm) and riser heights (0.5, 0.75 and 1 m) were used.